Tinjauan Yuridis Perkembangan Hukum Yang MengaturMengenai Perbankan Syariah Di Indonesia - Rachmatika, Nabella Chenia, Wardah Yuspin, S.H, Mkn, PhD (2017)
Nabella Chenia Rachmatika, NIM: C100130218, Fakultas Hukum Universitas Muhammadiyah Surakarta, Tahun 2017, Judul: "JURIDICAL REVIEW PROGRESS ON GOVERNING LAW ISLAMIC BANKING IN INDONESIA'' This study aims to determine the laws governing the development of Islamic banking in Indonesia, to determine the legal implications of the enactment of Act 21 of 2008 concerning Islamic Banking, to determine the comparative Act 21 of 2008 by Law Islamic Bank in Malaysia. The method I use is normative juridical approach. This type of research used by the author in this research is descriptive research. Using the types and sources of secondary data, which covers primary legal materials, secondary legal materials, tertiary legal materials. Methods of data collection in this study using the methods of literary study. Data analysis methods used by the author in this study is a qualitative method. Based on the results of research and discussion it can be concluded that at this time of banking institutions play an important role in economic development and has developed very rapidly. Conventional banking system that existed before become more complete with the system of Islamic banking or Islamic banking. Islamic banking industry develop faster after the issuance of Law No. 21 of 2008 concerning Islamic Banking. This law consists of 70 chapters and is divided into 13 bab.Undang Act is clearly evident is a guarantee for business certainty and legal protection that is necessary, because this law a legal umbrella for all people associated with Islamic banks.